INTERNALISASI NILAI PENDIDIKAN AGAMA ISLAM DALAM TRADISI PERNIKAHAN ADAT JAWA: KAJIAN FILOSOFIS DAN PRAKTIS - A. Faizul Mubarak; Lailul Vicky Zawawi Imron (LPPM STAI Muhammadiyah Probolinggo, 2026)
Javanese traditional wedding traditions are rich in symbolism and spiritual values, including Islamic religious education. However, the younger generation often perceives them merely as cultural rituals without understanding their religious significance. This study aims to explore the process of internalizing Islamic religious education values in Javanese traditional wedding traditions in Sukapura District, focusing on values of faith, worship, and morals, and their application in social life. The study uses a qualitative descriptive case study approach. Data collection was conducted through in-depth interviews with traditional leaders, religious leaders, and the families of the wedding organizers; participatory observation; and documentation. Each stage of the wedding procession, such as siraman, akad nikah, kacar-kucur, sungkeman, and sepasaran, contains philosophical and symbolic meanings that align with Islamic teachings. Traditions originally rooted in local culture have undergone spiritual transformation, such as the midodareni procession, which has been replaced by prayers and tahlil. These values are also internalized in family and community behaviors after marriage, seen through responsible behavior, respect for parents, and increased religious activities. This study offers a new understanding of the integration between local wisdom and Islamic education. It also serves as a reference for the development of culturally and religiously based educational curricula.